Influence of Adult Neural Crest-Derived Multipotent Stem Cells on Regeneration of Orbital Soft Tissue Content After Experimental Injury - Chepurnyi, Yuri V.; Kustrjo, T. V.; Korsak, Alina V.; Likhodievskyi, Volodymyr V.; Rodnichenko, Anzhela E.; Gubar, Olga S.; Zlatska, Olena V.; Kopchak, A. V.; Zabila, Anna O.; Olefir, Serhii S.; Zubov, Dmytro O.; Vasyliev, Roman G.; et al. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 059–063